2020
DOI: 10.1002/chem.202003283
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal FRET Assay Identifies Potent Drug‐Like Inhibitors of the Ceramide Transport Protein (CERT)

Abstract: Ceramide transfer protein (CERT) mediates non‐vesicular transfer of ceramide from endoplasmic reticulum to Golgi apparatus and thus catalyzes the rate‐limiting step of sphingomyelin biosynthesis. Usually, CERT ligands are evaluated in tedious binding assays or non‐homogenous transfer assays using radiolabeled ceramides. Herein, a facile and sensitive assay for CERT, based on Förster resonance energy transfer (FRET), is presented. To this end, we mixed donor and acceptor vesicles, each containing a different fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…To further strengthen this conclusion, another group pharmacologically inhibited CERT, which induced ceramide-dependent apoptosis in HeLa cells [191]. Recently, a new Förster resonance energy transfer-based ceramide assay was developed to identify new CERT inhibitors [192], which provides an opportunity to develop cancer therapeutics targeting this lipid transferase.…”
Section: Ceramide Transportmentioning
confidence: 99%
“…To further strengthen this conclusion, another group pharmacologically inhibited CERT, which induced ceramide-dependent apoptosis in HeLa cells [191]. Recently, a new Förster resonance energy transfer-based ceramide assay was developed to identify new CERT inhibitors [192], which provides an opportunity to develop cancer therapeutics targeting this lipid transferase.…”
Section: Ceramide Transportmentioning
confidence: 99%
“…Considering a number of candidate potent drug-like inhibitors that target the ceramide transport to the Golgi [35,39,61], the BRED 0.1 cell line would be expected to be convenient for in cellulo characterization of their pharmacodynamics. Other organelle targeting domains can be used in lieu of the PH domain to evaluate the transport of ceramide to other cellular organelles, such as mitochondria to study the function of ceramide in regulating mitochondria-mediated cell death [47] and to screen its potent drug-like inhibitors [39,47] This assay could potentially be expanded to study the intracellular trafficking of other metabolites for which appropriate fluorophore conjugates can be produced. The blue-shifted BODIPLY FL dye in combination with other acceptors such as red-shifted fluorophores can be an advantage when dual BRED monitoring is required to study complex signalling networks [27,62].…”
Section: Discussionmentioning
confidence: 99%
“…Specific inhibitors of CERT-mediated ceramide transport [35] are considered promising for combating cancerassociated multi-drug resistance [36], as well as different infectious diseases [37,38]. In our recent study, several potential inhibitors of ceramide intracellular transport were identified using the fluorescence-labelled ceramide (BODIPY-Cer) in a liposomal FRET assay [39]. However, most developed CERT inhibitors have not been tested in cells [40], mainly due to the lack of suitable assays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of HPA-12, a competitive inhibitor of CERT, helped a lot to understand the activity, function and regulation of CERT [34]. A recent study identified two others CERT inhibitors [35]. The authors used a fluorescence-based assay to measure the capacity of CERT to transfer labelled-ceramide to a liposome containing a lipid-quencher that can be tracked.…”
Section: New Cert Inhibitorsmentioning
confidence: 99%